The ethics of New Testament interpretation - Botha, J. (Neotestamentica, 1992)
This study is an attempt to develop and illustrate the concept of an ethos of responsible interpretation within the broader context of an 'ethics of historical reading' and an 'ethics of public accountability' in New Testament scholarship. It 'compels' the interpreter to take reading seriously. This implies that the implications of the linguisticality, literariness and rhetoricity of the text, as well as the social phenomena of the world created by the text, 'must' be honoured and studied with all possible methodological sophistication and rigour.